2018
DOI: 10.3961/jpmph.18.052
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Support and the Neighborhood Environment on Physical Activity in Low-income, Mexican-American Women in South Texas

Abstract: ObjectivesTo determine the relationships between physical activity (PA), the neighborhood environment support for PA, and social support for PA among Mexican-American women living in South Texas. The Enlace study was a randomized controlled trial that tested the effectiveness of a promotora-led PA intervention among low-income Mexican origin women (n=614) living in colonias.MethodsThe dependent measures included accelerometer-measured average moderate to vigorous physical activity (MVPA) and sedentary breaks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Originally, there were various other volunteers, such as health volunteers (15)(16)(17)(18)(19), district welfare commissioners (20), and voluntary disaster-prevention organizations (21), engaged in community-based activities according to their purposes. Several previous studies in Western countries have shown that community-based volunteer support for exercise and sports can cause neighborhood residents to increase activity levels (22)(23)(24). These findings support the usefulness of the Japanese CSL.…”
Section: Introductionsupporting
confidence: 74%
“…Originally, there were various other volunteers, such as health volunteers (15)(16)(17)(18)(19), district welfare commissioners (20), and voluntary disaster-prevention organizations (21), engaged in community-based activities according to their purposes. Several previous studies in Western countries have shown that community-based volunteer support for exercise and sports can cause neighborhood residents to increase activity levels (22)(23)(24). These findings support the usefulness of the Japanese CSL.…”
Section: Introductionsupporting
confidence: 74%
“…Additionally, the 6-month maintenance phase in our study is still relatively short, considering the notable lifestyle change asked of participants, who reported close to 0 min of MVPA/week upon enrollment. However, since only a few interventions for Latinas have examined PA maintenance for six or more months ( Salinas et al, 2018 , Arredondo et al, 2017 , Van Name et al, 2016 ), our study contributes to the lack of literature in this area. Future studies should examine longer follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…Main effect associations between the built environment and active transport were investigated in 38 studies (see Table 2 ), including 30 cross-sectional [ 43 , 46 , 58 , 59 , 62 , 65 , 73 , 78 , 81 83 , 85 , 87 , 90 , 92 – 94 , 97 – 100 , 102 , 105 , 107 , 112 , 119 , 122 , 124 126 ], three longitudinal [ 66 , 67 , 89 ], and five quasi-experimental studies [ 51 , 56 , 60 , 70 , 101 ], resulting in a total of 492 associations ( n = 402 in Western countries). The most frequent positive associations occurred for the multicomponent category ( n = 31 positive, n = 32 null associations), followed by destination accessibility ( n = 24 positive, n = 57 null associations), specifically for destination mix, parks, recreational facilities, and shops and services for daily living.…”
Section: Article Qualitymentioning
confidence: 99%